Efficacy and safety of inclisiran in stroke or cerebrovascular disease prevention: a systematic review and meta-analysis of randomized controlled trials - Luo, Min; Liu, Yihan; Xu, Xinyi; Liu, Kai; Shen, Chao; Hu, Haoyang; He, Zhiyao; Wu, Fengbo (Frontiers in Pharmacology, 2023)
Aims: As the impact of inclisiran in stroke prevention of atherosclerotic cardiovascular disease (ASCVD) or its high-risk patients is still unclear, we conducted a systematic review and meta-analysis of randomized controlled trials (RCT) to quantify inclisiran prevention effectiveness of stroke for these patients. Methods: A literature research was conducted in four electronic databases (PubMed, EMBASE, Web of Science, CENTRAL), and two clinical trials registers (ClinicalTrials.gov, WHO ICTRP) from the reception to 17 Oct 2022, and was updated by the end of the study on 5 Jan 2023. Two authors independently screened the studies, extracted the data and assessed the bias. Risk of bias was assessed by using Cochrane risk-of-bias tool for randomized trials (RoB 2). Intervention effect was estimated by calculating risk ratio (RR), weighted mean difference (WMD), and 95% confidence interval (CI) with R 4.0.5. Sensitivity analysis by changing pooled model was also performed to test the robustness of the pooled results. If above was not possible, a descriptive analysis would be conducted. Results: Four RCTs (n=3,713 patients) were rated as high-risk bias. Meta-analysis of three RCTs (ORION-9, ORION-10, and ORION-11) showed that inclisiran reduced myocardial infarction (MI) risk by 32% (RR=0.68, 95%CI=0.48~0.96), but did not reduce stroke (RR=0.92, 95%CI=0.54~1.58) and major cardiovascular events (MACE) (RR=0.81, 95%CI=0.65~1.02) risk. Sensitivity analysis showed results were stable. Safety was similar to placebo group but had frequent injection-site reactions (RR=6.56, 95%CI=3.83~11.25) which were predominantly mild or moderate. One RCT (ORION-5) was conducted a descriptive analysis for different study design, and suggested that inclisiran might be given semiannually from the beginning. Conclusion: Inclisiran was unbeneficial for stroke or MACE prevention in ASCVD or its high-risk patients, but was associated with reduction of MI. Since the insufficient number and quality of literatures and the non-standard definition of cardiovascular events, further studies are essential for confirming the results.